Whole Genome Sequencing Analysis to Identify Candidate Genes Associated With the rib eye Muscle Area in Hu Sheep - Zhao, Yuan; Zhang, Xiaoxue; Li, Fadi; Zhang, Deyin; Zhang, Yukun; Li, Xiaolong; Song, Qizhi; Zhou, Bubo; Zhao, Liming; Wang, Jianghui; Xu, Dan; Cheng, Jiangbo; et al. (Frontiers in Genetics, 2022)
In sheep meat production, the rib eye area is an important index to evaluate carcass traits. However, breeding using rib eye muscle area traits is difficult because of the long generation interval and difficult determination. Therefore, the present study used whole genome sequencing data to excavate candidate genes associated with the rib eye muscle. Male Hu sheep (n = 776) with pedigrees and 274 males with no pedigree were included. The genetic parameters of the rib eye area were estimated using a general linear mixed model. The rib eye area showed medium heritability (0.32 ± 0.13). Whole-genome sequencing of 40 large rib eye sheep and 40 small rib eye sheep was performed. Case-control genome-wide association studies and the fixation index identified candidate rib eye associated genes. Seven single nucleotide polymorphisms (SNPs) in six genes (ALS2, ST6GAL2, LOC105611989, PLXNA4, DPP6, and COL12A1) were identified as candidates. The study population was expanded to 1050 to perform KASPar genotyping on five SNPs, which demonstrated that SNPs in LOC105611989, DPP6, and COL12A1 correlated significantly with the rib eye area, which could be used as genetic markers for molecular breeding of the rib eye area. The results provided genetic parameters estimated on the rib eye area and information for breeding based on carcass traits in Hu sheep.